2009
DOI: 10.1111/j.1365-3156.2008.02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Avascular osteonecrosis after treatment of SARS: a 3‐year longitudinal study

Abstract: Summaryobjective To investigate the relationship between avascular osteonecrosis (AVN) and corticosteroid treatment given to patients with severe acute respiratory syndrome (SARS).methods Longitudinal study of 71 former SARS patients (mainly health care workers) who had been treated with corticosteroids, with an observation time of 36 months. Magnetic resonance images (MRI) and X-rays of hips, knees, shoulders, ankles and wrists were taken as part of the post-SARS follow-up assessments.results Thirty-nine per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 17 publications
0
40
0
5
Order By: Relevance
“…given to SARS patients through a longitudinal study of 71 SARS patients (mainly HCWs) who had been treated with corticosteroids, with an observation time of 36 months. 25 Magnetic resonance images and X-rays of the hips, knees, shoulders, ankles and wrists were taken as part of the post-SARS follow-up assessments. Thirty-nine percent developed AVN of the hips within 3-4 months after starting treatment.…”
Section: Consequences Of the Epidemicmentioning
confidence: 99%
“…given to SARS patients through a longitudinal study of 71 SARS patients (mainly HCWs) who had been treated with corticosteroids, with an observation time of 36 months. 25 Magnetic resonance images and X-rays of the hips, knees, shoulders, ankles and wrists were taken as part of the post-SARS follow-up assessments. Thirty-nine percent developed AVN of the hips within 3-4 months after starting treatment.…”
Section: Consequences Of the Epidemicmentioning
confidence: 99%
“…Ten studies including a total of 1137 SARS patients (with a mean/median age of between 30.0 and 47.0 years) met the inclusion criteria and entered final meta-analysis, of which 304 patients developed osteonecrosis. Seven articles [11,12,14,15,[17][18][19] were published in Chinese, and 3 [13,16,20] were published in English. Seven studies reported the number of osteonecrosis cases in both male and female patients.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The wide use of steroids resulted in the development of serious side effects in many recovered SARS patients, including osteonecrosis [9,10]. However, the relationship between steroid therapy and osteonecrosis remains unclear, partly because although a number of studies had reported the prevalence of steroid-related osteonecrosis in recovered patients [11][12][13][14][15][16][17][18][19][20][21][22][23], some of them failed to address the regimens used [21][22][23]. The absence of information regarding steroid administration regimens prevented researchers from making precise evaluations of this link.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al investigated the relationship between avascular osteonecrosis (AVN) and corticosteroid treatment given to patients with SARS through a longitudinal study of 71 former SARS patients (mainly HCWs) who had been treated with corticosteroids, with an observation time of 36 months. 22 Magnetic resonance images and X-rays of hips, knees, shoulders, ankles and wrists were taken as part of the post-SARS follow-up assessments. Thirty-nine per cent (39%) developed AVN of the hips within 3-4 months after starting treatment.…”
Section: Consequences Of the Epidemicmentioning
confidence: 99%
“…The sole factor explaining AVN in the hip was the total dose of corticosteroids received, which ranged from 1000 to 10 000 mg for the majority of cases, but was as high as 25 000 in some cases. 22 The use of corticosteroids as well as other drugs (e.g. rib- Lessons learnt and actions taken in China regarding epidemic preparedness…”
Section: Consequences Of the Epidemicmentioning
confidence: 99%